Distinct microglial response against Alzheimer's amyloid and tau pathologies characterized by P2Y12 receptor. Issue 1 (29th January 2021) - Maeda, Jun; Minamihisamatsu, Takeharu; Shimojo, Masafumi; Zhou, Xiaoyun; Ono, Maiko; Matsuba, Yukio; Ji, Bin; Ishii, Hideki; Ogawa, Masanao; Akatsu, Hiroyasu; Kaneda, Daita; Hashizume, Yoshio; et al.
Abstract: Microglia are the resident phagocytes of the central nervous system, and microglial activation is considered to play an important role in the pathogenesis of neurodegenerative diseases. Recent studies with single-cell RNA analysis of CNS cells in Alzheimer's disease and diverse other neurodegenerative conditions revealed that the transition from homeostatic microglia to disease-associated microglia was defined by changes of gene expression levels, including down-regulation of the P2Y12 receptor gene ( P2Y12R ). However, it is yet to be clarified in Alzheimer's disease brains whether and when this down-regulation occurs in response to amyloid-β and tau depositions, which are core pathological processes in the disease etiology. To further evaluate the significance of P2Y12 receptor alterations in the neurodegenerative pathway of Alzheimer's disease and allied disorders, we generated an anti-P2Y12 receptor antibody and examined P2Y12 receptor expressions in the brains of humans and model mice bearing amyloid-β and tau pathologies. We observed that the brains of both Alzheimer's disease and non-Alzheimer's disease tauopathy patients and tauopathy model mice (rTg4510 and PS19 mouse lines) displayed declined microglial P2Y12 receptor levels in regions enriched with tau inclusions, despite an increase in the total microglial population. Notably, diminution of microglial immunoreactivity with P2Y12 receptor was noticeable prior to massive accumulations of phosphorylated tau aggregates and neurodegeneration in rTg4510 mouse brains, despite a progressive increase of total microglial population. On the other hand, Iba1-positive microglia encompassing compact and dense-cored amyloid-β plaques expressed P2Y12 receptor at varying levels in amyloid precursor protein (APP) mouse models (APP23 and App NL-F/NL-F mice). By contrast, neuritic plaques in Alzheimer's disease brains were associated with P2Y12 receptor-negative microglia. These data suggest that the down-regulation of microglia P2Y12 receptor, which is characteristic of disease-associated microglia, is intimately associated with tau rather than amyloid-β pathologies from an early stage and could be a sensitive index for neuroinflammatory responses to Alzheimer's disease-related neurodegenerative processes. Abstract : Homeostatic microglial marker P2Y12 receptor was accumulated around amyloid plaques in mouse models; this receptor was reduced in tauopathy mouse models prior to massive tangle formation. The down-regulation of P2Y12 receptor could be a sensitive index for neuroinflammatory responses to tau-induced neurodegeneration. Graphical Abstract: